The impact of low-dose Fructooligosaccharide combined with Mesalazine on inflammation levels and therapeutic effects in elderly patients with ulcerative colitis - Wang Fangfang; Ji Xiaoyan; Li Chunhua; Cui Min (Guoji laonian yixue zazhi)
[Objective] To analyze the therapeutic effects, inflammation levels, and safety evaluation of low-dose Fructooligosaccharide combined with Mesalazine in elderly patients with ulcerative colitis. [Methods] Ninety elderly patients with ulcerative colitis treated in the First teaching Hospital of Xinjiang Medical University from January 2021 to January 2023 were included and randomly divided into a treatment group and a control group, with 45 patients in each. Both groups received routine treatment upon admission and oral Mesalazine enteric-coated tablets. The treatment group additionally received low-dose Fructooligosaccharide oral solution for 4 weeks. Therapeutic effects, levels of high-sensitivity C reactive protein (hs-CRP), interleukin-8 (IL-8), and tumor necrosis factor-α (TNF-α) in serum, and incidence of adverse reactions such as nausea, vomiting, and skin itching were compared. [Results] The total effective rate in the treatment group was 88.89%(40/45), it was significantly higher than the 64.44%(29/45) in the control group (P<0.05). There was no significant difference in hs-CRP, IL-8, and TNF-α levels between the two groups before treatment (P>0.05). After treatment, inflammatory marker levels in the treatment group were significantly lower than those in the control group (P<0.05). The incidence of adverse reactions was 13.33% in the treatment group and 11.11% in the control group, with no significant difference between the two groups (P>0.05). [Conclusion] Low-dose Fructooligosaccharide combined with Mesalazine can significantly improve therapeutic effects and reduce inflammation in elderly patients with ulcerative colitis, with a high level of safety.